Cavernous Lymphangioma in the Maxillary Sinus. Issue 8 (November 2019) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract : Abstract: Lymphangioma in the maxillary sinus is rare. Herein, the authors report an unusual case of cavernous lymphangioma, in the maxillary sinus, with imaging examinations. Clinicians should be aware of the possibility of lymphangioma in the maxillary sinus, and be capable of distinguishing it, from other benign cystic lesions.